Spiritualisasi Keilmuan: Mengkonstruksi Peradaban Intelektual Muslim Abad Ke-21 - Mohammad Miftahusyai'an (UIN Maulana Malik Ibrahim Malang, 2010)
Western scholars who separate between science and religion have brought people in the final point of civilization. Therefore, the duty of Moslem scholar in the 21th century is to rebuild the spiritual intellectual integrity in the frame of science and civilization. The main responsibility of Moslem scholars, nowadays, in reaching the brightness of life is reconstructing science paradigm by relocating God as the main stream of thought. The bright time of Madinah civilization is the starting point of the glory of Islamic civilization which successfully has entered all over the world. Therefore, intellectual orientation which has become Moslem’s responsibility is to reform the principles of Madinah civilization to be reconstructed to the present time. This is very important issue as Madinah civilization has not established yet that will be possible for Moslem scholars can speak much about the 21th century civilization. At the beginning of Islam period, the fight proposed by Moslem scholars was deconstructed the jahiliyah’s way of thinking, furthermore, the great jihad of Moslem scholars in the present time is reconstructing the scientific way of thinking which is currently empirical-minded. Moreover, the Moslem scholar’s responsibility is to present spiritualism in scientific discourse. The integration of science and religion has become conceptualization of his science, hence, al Quran will be always the eternal source of science. Sarjana Barat yang memisahkan antara sains dan agama telah membawa orang di titik akhir peradaban. Oleh karena itu, tugas sarjana Islam di abad ke 21 adalah membangun kembali integritas intelektual spiritual dalam kerangka sains dan peradaban. Tanggung jawab utama ulama Muslim, saat ini, dalam mencapai kecerahan hidup adalah merekonstruksi paradigma sains dengan merelokasi Tuhan sebagai aliran pemikiran utama. Waktu cemerlang peradaban Madinah menjadi titik awal dari kemuliaan peradaban Islam yang telah berhasil masuk ke seluruh dunia. Oleh karena itu, orientasi intelektual yang telah menjadi tanggung jawab umat Islam adalah mereformasi prinsip peradaban Madinah untuk direkonstruksi hingga saat ini. Ini adalah isu yang sangat penting karena peradaban Madinah belum terbentuk, yang mungkin bagi ulama Islam dapat berbicara banyak tentang peradaban abad 21. Pada awal periode Islam, pertarungan yang diajukan oleh para ilmuwan Muslim mendekonstruksi cara berpikir jahiliyah, jihad besar ulama Muslim saat ini sedang membangun kembali cara berpikir ilmiah yang saat ini bersifat empiris. Lebih dari itu, tanggung jawab ilmuwan Muslim adalah menyajikan spiritualisme dalam wacana ilmiah. Integrasi sains dan agama telah menjadi konseptualisasi sainsnya, oleh karena itu, al Quran akan selalu menjadi sumber sains abadi.